Intizar ke Jihad: Paradigma Islam Protes dalam Pemikiran Ali Syari’ati - Saifullah, Saifullah; Amin, Saidul; Kasmuri, Kasmuri; Jasman, Febrina Alya; Anggraini, Putri (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This study analyzes the paradigm of protest Islam in the thought of Ali Syari’ati through the conceptual transformation from intizar to jihad. It aims to explain how Syari’ati reconstructs the meaning of intizar (awaiting) from a passive eschatological attitude into a historical consciousness that critically engages with social injustice. Within this framework, intizar is not understood as a fatalistic stance, but rather as a theological and ethical foundation for committed struggle. Furthermore, this research demonstrates that jihad in Syari’ati’s perspective is not merely physical warfare, but an intellectual, moral, and social struggle to uphold tawhid and to liberate the oppressed (mustadh‘afin) from structures of domination. Islam is thus conceived as a revolutionary force that stands for justice and rejects the religious legitimation of political tyranny and economic inequality. In this context, the role of the enlightened intellectual (raushanfikr) becomes central as an agent of social transformation who awakens the collective consciousness of the community. Using a qualitative library-based approach, this study affirms that the integration of intizar and jihad forms an ideological framework of Islam that is active, critical, and transformative. This paradigm positions faith as a liberating energy that demands concrete engagement in social struggle, so that true awaiting gains meaning only when embodied in action aimed at realizing justice and historical change.Keywords: Ali Syari’ati, intizar, jihad, protest Islam, social transformation. Abstrak: Penelitian ini menganalisis paradigma Islam protes dalam pemikiran Ali Syari’ati melalui transformasi konseptual dari intizar menuju jihad. Penelitian ini bertujuan menjelaskan bagaimana Syari‘ati merekonstruksi makna intizar (penantian) dari sikap eskatologis yang pasif menjadi kesadaran historis yang kritis terhadap ketidakadilan sosial. Dalam kerangka tersebut, intizar tidak dimaknai sebagai sikap fatalistik, melainkan sebagai fondasi teologis dan etis bagi komitmen perjuangan.Lebih lanjut, penelitian ini menunjukkan bahwa jihad dalam perspektif Syari‘ati bukan sekadar perang fisik, tetapi perjuangan intelektual, moral, dan sosial untuk menegakkan tauhid serta membebaskan kaum tertindas (mustadh‘afin) dari struktur penindasan. Islam dipahami sebagai kekuatan revolusioner yang berpihak kepada keadilan dan menolak legitimasi religius atas tirani politik maupun ketimpangan ekonomi. Dalam konteks ini, peran intelektual tercerahkan (raushanfikr) menjadi sentral sebagai agen transformasi sosial yang membangkitkan kesadaran kolektif umat.Dengan pendekatan kualitatif berbasis studi kepustakaan, penelitian ini menegaskan bahwa integrasi intizar dan jihad membentuk kerangka ideologis Islam yang aktif, kritis, dan transformatif. Paradigma ini menempatkan iman sebagai energi pembebasan yang menuntut keterlibatan nyata dalam perjuangan sosial, sehingga penantian sejati hanya bermakna ketika diwujudkan dalam aksi untuk menghadirkan keadilan dan perubahan historis.Kata kunci: Ali Syari‘ati, intizar, jihad, Islam protes, transformasi sosial.